1994
DOI: 10.1002/bms.1200230307
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactamase ragged ends detected by electrospray mass spectrometry correlates poorly with multiple banding on isoelectric focusing

Abstract: Purified preparations of TEM-2, P99, Bacillus cereus I and B. cereus II beta-lactamases were examined by electrospray (ES) mass spectrometry. The ES mass spectra of the B. cereus enzymes revealed the presence of four to five components of different mass, corresponding to the loss of different numbers of N-terminal amino acids (ragged ends). The ES mass spectra of both TEM-2 and P99 consisted of a single component with no evidence of ragged ends. All four beta-lactamase preparations were visualized on isoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…To verify the hypothesis that GOB-1 has ragged ends (not a unique phenomenon with respect to MBLs [32]), the N-terminus of the enzyme was sequenced. The presence of two N-terminal sequences QVVKE and LNAQV confirmed that the signal peptide was cleaved at two positions.…”
Section: Ms and N-terminal Sequencing Of Wild-type Gob-1mentioning
confidence: 99%
“…To verify the hypothesis that GOB-1 has ragged ends (not a unique phenomenon with respect to MBLs [32]), the N-terminus of the enzyme was sequenced. The presence of two N-terminal sequences QVVKE and LNAQV confirmed that the signal peptide was cleaved at two positions.…”
Section: Ms and N-terminal Sequencing Of Wild-type Gob-1mentioning
confidence: 99%
“…has been utilized previously to characterize inhibitors covalently bound to serine ␤-lactamases (2,9,19). Although the substrate hydrolysis of metallo-␤-lactamases is not expressed by means of covalent intermediates, the presence of a cysteine residue close to the active site of metallo-␤-lactamases affords the prospect of covalent intervention at this residue in achieving inhibition.…”
Section: Esms and Preparation Of Samples Electrospray Mass Spectroscmentioning
confidence: 99%
“…ESMS of the B. cereus II enzyme gave 6 peaks, A through F (Fig. 2), each of which corresponded to ragged ends comprising the loss of N-terminal amino acid residues (19). Following a 1:10,000 dilution, B. cereus II enzyme was inhibited 95% by each of the inhibitors, SB214751, SB214752, or SB213079.…”
Section: Activities Of Compounds Sb214751 Sb214752 Sb213079mentioning
confidence: 99%
“…ESI-MS of intact KPC-2 ␤-lactamase revealed that multiple forms of the KPC-2 ␤-lactamase are produced when the full-length protein is expressed in E. coli (data not shown). Thus, the N terminus of KPC-2 appears ragged when expressed in E. coli DH10B or Origami2 DE3 pLys (32,38). All purified forms of KPC-2 behaved identically in kinetic assays (data not shown).…”
Section: Resultsmentioning
confidence: 91%